Identificación de los factores sociales en la decisión de compra de los clientes de muebles de madera de la Empresa Slim Diseño. - Chicaiza Cando, Jessica Patricia (2018)
In this research project, the most relevant social factors in the decision to purchase wooden furniture were determined, considering that nowadays companies should take into account consumer behavior since this is based on preferences, tastes, and product information searching and in turn companies can establish strategies to achieve a position in the consumer's mind since the market has strong competition in the furniture sector. The lack of knowledge of consumer behavior has hindered success in companies; the objective of the research was to determine the most relevant social factors in the decision to purchase wood furniture from the Slim Design Company, applying research methodologies and obtaining necessary information from the population under study, the most relevant social factors in the purchase decision was determined through the application of a questionnaire, it was concluded that in the purchase decision process, the family is a whole who make the decision on the purchase of furniture, looking for options and analyze the alternatives and characteristics to make the best choice, therefore determine the social factors that in one way or another will benefit the company to bring new customers to increase the frequency of purchase and improve the level of sales.